Pergeseran Makna Sifat Melawan Hukum Dalam Tindak Pidana Korupsi - Muhammad Rutabuz Zaman (MASADIR: Jurnal Hukum Islam, 2021)
The meaning of being against the law (wederrechtelijkheid) has shifted several times from being against the law in a formal sense (formele wederrechtelijkheid) to include being against the law in a material sense (materialele wederrechtelijkheid). From the nature of 'against the law' in the material sense (materialele wederrechtelijkheid) which functions negatively, it shifts to include the nature of 'against the law' in the material sense which functions positively and then again shifts to the nature of 'against the law' in the material sense which functions negatively. This is due to none other than the fact that judges in examining, adjudicating and deciding cases are required to explore, follow and understand the values of law and justice that live in society, in addition to the existence of the House of Representatives as a legislative power, which has the authority to make new laws and other authorities. The Constitutional Court in conducting a judicial review of the law against the 1945 Constitution Cq the Corruption Act.